Balkan Babel : the disintegration of Yugoslavia from the death of Tito to the fall of Milosevic - Ramet, Sabrina P., 1949- (Boulder : Westview Press, 2002)
Yugoslavia's would-be system-builders failed three times over to build a workable system. The underlying problem was their failure to resolve the problem of legitimacy. In the 1980s, economic deterioration pushed people to despair and, under the pressure of Serbia's ambitious political establishment, the country broke up along ethnic fault lines. This volume, now in its fourth expanded edition, tells the story of socialist Yugoslavia's troubles and the challenges facing its successor states from May 1980 to July 2001.
Political debate, 1980-1986 -- The gathering storm, 1987-1989 -- Brotherhood and disunity, 1989-1991 -- The Catholic Church -- The Serbian Orthodox Church -- Islam -- Rock music -- Serbia and Croatia at war again -- On their own: Slovenia and Macedonia since 1991 -- The struggle for Bosnia -- Repercussions of the war in religion, gender relations, and culture -- Peace of Dayton -- Milošević, Kosovo, and the principle of legitimacy -- Serbia's unending crisis -- Epilog: The legitimacy problem
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 20. století; jugoslávská válka (1991-1995); Yugoslav War (1991-1995); Jugoslávie -- dějiny; Jugoslávie -- společenské poměry; Jugoslávie -- etnické vztahy; Yugoslavia -- history; Yugoslavia -- social conditions; Yugoslavia -- ethnic relations; monografie; e-knihy online; monographs; e-books online